Ijma' dan Problematikanya - Ansori, Ansori (Fakultas Syariah IAIN Purwokerto, 2007)
Ushul fiqh experts divided the sources of Islamic law into two main categories: main source and supported source. The main sources are Al Qur’an and sunnah Muhammad SAW. In the past, Muhammad SAW prophet handled his followers himself. After he passed away, ‘ijma among his companions holds important role beside Al-Qur’an and al Sunnah. Agreement in laws and politics areas inspired Moslems scholars to regard ‘ijma as secondary reference beside qiyas (analogy).